Tribological performance of steel guideway with biomimetic hexagonal micro-textures. (2nd July 2020) - Zhang, Yun; Deng, Jianxin; Meng, Ying; Yue, Hongzhi
ABSTRACT: An Nd:YAG laser was used to fabricate biomimetic hexagonal micro-textures on the mating surfaces of steel guideways. The influence of the micro-textures under grease lubrication on the tribological performances of guideways was determined using a guideway reciprocating sliding tester facility for different micro-textures distributions and orientations, loads and sliding speeds. Results revealed that biomimetic hexagonal micro-textures had a positive influence on the tribological properties of guideway when only one surface was textured, but they would play the opposite role if both of the mating surfaces were textured. The friction coefficient of one-side-textured guideways was reduced and the wear was improved in comparison to polished guideways. Moreover, on the condition of higher loads and sliding speeds, the micro-textures in which two sides of each hexagon are perpendicular to the sliding direction of the guideway showed the optimal tribological properties due to the hydrodynamic effect.